2005
DOI: 10.1016/j.str.2005.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Activation for Transcription Factor PhoB Suggested by Different Modes of Dimerization in the Inactive and Active States

Abstract: Response regulators (RRs), which undergo phosphorylation/dephosphorylation at aspartate residues, are highly prevalent in bacterial signal transduction. RRs typically contain an N-terminal receiver domain that regulates the activities of a C-terminal DNA binding domain in a phosphorylation-dependent manner. We present crystallography and solution NMR data for the receiver domain of Escherichia coli PhoB which show distinct 2-fold symmetric dimers in the inactive and active states. These structures, together wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
198
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(215 citation statements)
references
References 52 publications
14
198
0
2
Order By: Relevance
“…2a). Consistent with phosphorylation-induced dimerization in RRs of the OmpR/PhoB family (Bachhawat et al, 2005), incubation of RR468 with acetyl phosphate induces a band shift. In contrast, 6His-NblR-RD and 6His-NblR did not change in mobility, suggesting that these proteins were not phosphorylated.…”
Section: Nblr Is Not Phosphorylated In Vitro By Acetyl Phosphatementioning
confidence: 59%
See 1 more Smart Citation
“…2a). Consistent with phosphorylation-induced dimerization in RRs of the OmpR/PhoB family (Bachhawat et al, 2005), incubation of RR468 with acetyl phosphate induces a band shift. In contrast, 6His-NblR-RD and 6His-NblR did not change in mobility, suggesting that these proteins were not phosphorylated.…”
Section: Nblr Is Not Phosphorylated In Vitro By Acetyl Phosphatementioning
confidence: 59%
“…The quality of the final model was assessed using the PROCHECK suite of programs (Morris et al, 1992). The receiver domain structures of phosphorylated Spo0A from Bacillus stearothermophilus (RCSB code 1QMP) (Lewis et al, 1999), beryllium fluoride-activated PhoB from E. coli (RCSB code 1ZES) (Bachhawat et al, 2005), FrzS from Myxococcus xanthus (RCSB code 2GKG) (Fraser et al, 2007), beryllium fluoride-activated CheY from E. coli (RCSB code 1FQW) , HP1043 from Helicobacter pylori (RCSB code 2PLN) as well as the NblR model were structurally aligned using the LSQKAB program as implemented in the CCP4 suite (Collaborative Computational Project, Number 4, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…The two PhoB N dimers have been extensively characterized both structurally and biochemically (26 -29). As expected, a dimer along the ␣4-␤5-␣5 surface (here termed dimer 1) forms in the presence of a phosphoryl group analog (29) and represents the functional, phosphorylation-mediated dimer. Unexpectedly, metal binding alone supports a modified version of dimer 1 (27).…”
mentioning
confidence: 54%
“…Thus, we sought an alternative method of assessing communication between PhoB N active sites by examining binding of a phosphoryl group analog. BeF 3 Ϫ binds to the active site of response regulators and mimics the Asp-phosphate linkage of phosphorylated response regulators (22,29,47). A plot of the quench in PhoB N tryptophan fluorescence versus BeF 3 Ϫ concentration (Fig.…”
Section: Initial Analysis Of Phob N Autophosphorylation Suggested Posmentioning
confidence: 99%
“…Several DBD-DNA complex structures revealed that DBDs bind to promoter DNA sequences in a head-to-tail manner [13][14][15] . It was also suggested that the flexible linker connecting the REC and DBD should allow the DBD to bind to DNA in any orientation, as dictated by the DNA sequence or protein-protein interaction specifically between DBDs 16 . However, the flexible linker may introduce high mobility of the complex and hamper crystal structure study of activated response regulators.…”
mentioning
confidence: 99%